Rasionalitas Gerakan Kewirausahaan Organisasi Tarekat Ṣiddîqîyah di Jombang - Misbahul Munir (Islamica: Jurnal Studi Keislaman, 2015)
This article aims to reveal the values of local wisdom explored from the teachings of the Siddîqîyah order which drives the emergence of high spirit of entrepreneur-ship. The article demonstrates that the spirit of entrepreneur-ship within the Siddîqîyah order is strongly related to its teachings, doctrines and culture, such as that of the unity between faith and humanity, the eight points of readiness for the Siddîqîyah membership, and the doctrine of santri (disciple). In attempts to earn living, they run business enterprise through promoting the principle of hard-work and good business management, in addition to implementing spiritual and social capital in achieving success in business. They believe in and feel the strength of prayer (dua), certain rituals, and the importance of belief and harmony to achieve success in business. The teachings, doctrines and culture of the Sidd?q?yah order influence the understanding towards the meaning of wealth or property, and occupy an important position in the life of the Sidd?q?yah followers. For them, property or wealth has double meaning; it is not only meant in economic context, but also understood in other meanings, i.e., social, spiritual, cultural, and philosophical.